2013
DOI: 10.1089/end.2013.0025
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High Shock Number on Acute Complication Development After Extracorporeal Shockwave Lithotripsy

Abstract: At high voltage, high shock number was not shown to cause higher rates of short-term postoperative complications, as experienced by patients, when SWL was successful or resulted in a residual stone, yet complication rates associated with residual stone burden were approximately five times as common. Forgoing a higher shock number in the presence of a residual stone may therefore increase the risks of sequelae immediately after SWL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Previous studies have found that renal injury may exist after SWL [61,62]. Moreover, complications after an unsuccessful SWL procedure occurred at nearly five times the frequency [63]. A study has shown that an SWL monotherapy approach had a lower stone-free rate and a higher incidence of sepsis compared to PCNL [64].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that renal injury may exist after SWL [61,62]. Moreover, complications after an unsuccessful SWL procedure occurred at nearly five times the frequency [63]. A study has shown that an SWL monotherapy approach had a lower stone-free rate and a higher incidence of sepsis compared to PCNL [64].…”
Section: Discussionmentioning
confidence: 99%
“…Ureteroscopy has been increasingly favoured for the treatment of upper ureteral stones because of its high success rate within a short period of time, which is facilitated by the use of miniature surgical instruments, increased imaging quality and the effective use of laser technology, all of which are parallel to the advancing technology in the field [ 3 ]. Well-known evidence shows the potential risk of renal injury after repeated treatment of kidney stones with SWL [ 4 ], but no evidence of a similar risk for ureteral stones exists because of the lack of involvement of renal parenchyma in the shock wave exposure.…”
Section: Introductionmentioning
confidence: 99%
“…It is well documented that shock wave elicits renal damage and causes several short-term or long-term complications 1-3. Many clinical trials and animal models have been used to investigate the potential mechanism of shock wave injury to renal cells 4, 5.…”
Section: Introductionmentioning
confidence: 99%